Characteristics Associated with Engagement in the Early Detection Cascade of Care for Psychosis at a College Counseling Center. - Barans, Sam; Saavedra, Justine L.; Lardier, David T.; Tohen, Mauricio; Lenroot, Rhoshel; Bustillo, Juan; Halperin, Dawn; Friedman, Bess; Loewy, Rachel; Murray-Krezan, Cristina; McIver, Stephanie; Crisanti, Annette S. (Community Mental Health Journal, 2025)
Using the Cascade of Care framework, we explored the demographic and clinical characteristics of students at six stages in an early psychosis detection program at a college counseling center, with a focus on the transition between stages with the highest disengagement. We detailed and compared the demographic and clinical characteristics of those who (1) completed the Prodromal Questionnaire-Brief (PQ-B, N = 1588); (2) met the PQ-B cutoff score (n = 486); (3) were referred for secondary phone screening (n = 404); (4) completed secondary phone screening (n = 198); (5) completed a Coordinated Specialty Care (CSC) eligibility assessment (n = 51); and (6) were enrolled in CSC (n = 21). Education level and gender identity were associated with engagement at multiple stages of the early detection cascade. Graduate education level, transgender or gender diverse gender identity, alcohol use, and depressive symptoms predicted student follow-through with referral to secondary phone screenings.